2016
DOI: 10.1037/abn0000141
|View full text |Cite
|
Sign up to set email alerts
|

The role of interpersonal conflict and perceived social support in nonsuicidal self-injury in daily life.

Abstract: Although accumulating microlongitudinal research has examined emotion regulatory models of nonsuicidal self-injury (NSSI), few studies have examined how interpersonal contingencies influence daily NSSI behavior. Participants with repeated NSSI (N = 60) provided daily ratings of perceived social support, interpersonal conflict, and NSSI urges and behaviors for 14 days. Consistent with interpersonal models of NSSI, we hypothesized that participants would be more likely to engage in NSSI on days when they experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 45 publications
(93 reference statements)
12
91
1
Order By: Relevance
“…A reason for the pronounced peek for NSSI pictures could be that adolescents most often engage in NSSI in the evening and the urge for engaging in NSSI is highest in the evening. This is in line with recent findings that NSSI is associated with negative emotions during evening times (Turner et al 2016). Also, posting NSSI pictures around the evening hours and early in the morning before going to school might be associated with rising levels of stress before having to go to school.…”
Section: Discussionsupporting
confidence: 92%
“…A reason for the pronounced peek for NSSI pictures could be that adolescents most often engage in NSSI in the evening and the urge for engaging in NSSI is highest in the evening. This is in line with recent findings that NSSI is associated with negative emotions during evening times (Turner et al 2016). Also, posting NSSI pictures around the evening hours and early in the morning before going to school might be associated with rising levels of stress before having to go to school.…”
Section: Discussionsupporting
confidence: 92%
“…Procedures for this study are described in detail in Turner et al (2016). Briefly, after completing baseline self-report measures during a laboratory session, participants logged in to a secure, online portal each evening to complete diaries for fourteen days.…”
Section: Methodsmentioning
confidence: 99%
“…Participants from this study were drawn from a larger investigation of the emotional and interpersonal context of NSSI (see Turner et al, 2016). Young adults (N = 60, aged 18 to 35) recruited from community websites and post-secondary campuses were eligible to participate if they endorsed recent and repeated NSSI, as indicated by a) at least ten lifetime NSSI episodes, b) at least one NSSI episode in the past 12 months, and c) thoughts or urges for NSSI within the past two weeks.…”
Section: Participantsmentioning
confidence: 99%
“…As described in a previous study (Turner et al, 2016), given the strong withinperson correlations between the Valence and Calmness scales, we created a composite score by averaging these two z-transformed subscales to index daily negative affect, with higher scores indicating more negative and higher arousal emotional states. Previous research supports the within-and between-person reliability of the MDMQ, as well as its sensitivity to changes in mood within and between days (Wilhelm & Schoebi, 2007).…”
Section: Daily Measures Of Interpersonal Competence and Functioningmentioning
confidence: 99%
“…For instance, individuals who use NSSI to elicit soothing from others may struggle to get this need met in other ways, perhaps due to deficits in their social skills repertoire, problems in the responsiveness of their interpersonal environment, or both (Nock, 2008). Although previous studies have found that interpersonal functions of NSSI are endorsed less often and less strongly than intrapersonal functions (Klonsky, 2007), recent findings suggest that interpersonal reinforcement may nonetheless be important for understanding and predicting daily episodes of NSSI (Turner, Cobb, Gratz, & Chapman, 2016). Thus, previous work examining the interpersonal functions of NSSI provides clues about the specific interpersonal tasks that may be most difficult for individuals with NSSI and most relevant to NSSI behavior.…”
mentioning
confidence: 99%